Granting of Organic Fertilizer and NPK Fertilizer to Growth and Results of Sweet Corn (Zea Mays. L) - Hidayati, Sri; Ali, Mahrus; Purwanti, Sri; Huda, Nurul; ., Nurlina (International Journal of Engineering and Technology, 2018)
The aim of research is to test the combination of organic fertilizer and NPK fertilizer, test organic fertilizer, test NPK fertilizer that is suitable for the growth and yield of sweet corn. This research method using Randomized Block Design (RAK) arranged factorial consists of two factors, namely Organic Fertilizer (cage) with 3 levels of treatment (K) and NPK Fertilizer with 3 levels of treatment (M). Each treatment was repeated 3 times and each treatment combination consisted of two sample plants. The results of this study showed that the overall treatment of the combination of organic fertilizer and NPK fertilizer on the growth and yield of sweet corn plants did not show a real effect. Separately the treatment of organic fertilizer gave a very real effect on all observation variables, the average organic fertilizer as much as 17.5 tons / ha or 1.5 kg / tan (K3) gave the highest growth and yield of sweet corn compared to other treatment, Separately the treatment of NPK fertilizer gave a very real influence on all observation variables, the average NPK fertilizer with a composition of 450 kg Urea + 150 kg TSP + 75 kg KCl) / Ha or 9 g + 3 g + 1.5 g / tan (M3) gives the highest growth and yield of sweet corn compared to other treatments. Person.Â